FAKTOR RISIKO PERSALINAN SEKSIO CAESARIA DI RUMAH SAKIT Dr. SOEDIRMAN KEBUMEN - Sumarni Sumarni; Fitria Prabandari; Dyah Fajarsari (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Delivery by Cesarean section (SC) has a five times greater risk of complications than normal delivery. Maternal mortality due to surgical infection is 80 times higher than vaginal delivery, while complications of anesthesia are around 10% of maternal mortality. The purpose of this study was to determine the risk factors that influence SC deliveries at Dr. Soedirman Kebumen. The type of research used is analytic observational with a case control approach. The population in this study were all mothers who gave birth at the RSDS in January 2021-December 2021. The determination of the sample size was carried out using the unpaired categorical analytic formula with a sample size of 156. The data analysis used was to determine the relationship between the independent and dependent variables using Chi square nonparametric statistical test. The results of the study stated that severe pre-eclampsia had an effect of 4,405 times on pregnant women to be able to give birth to SC , prolonged labor had an effect of 4,104 times on pregnant women to be able to give birth to SC. Fetal Distress has a significant effect on the occurrence of SC deliveries. (p=0.007), History of SC had an effect of 6,452 more CS births, Pregnant women with Covid 19 had a significant effect on the occurrence of CS deliveries, Premature rupture of membranes had an effect of 14,000 times on pregnant women for can give birth to SC. Conclusion; Premature rupture of membranes has the highest risk of giving birth by CS.